An Update on the Immunotherapy for Oropharyngeal Squamous Cell Carcinoma - Huang, Yaxuan; Lan, Yunyun; Zhang, Zhe; Xiao, Xue; Huang, Tingting (Frontiers in Oncology, 2022)
Oropharyngeal squamous cell carcinoma (OPSCC) is a kind of head and neck cancer that is very uncommon globally. Remarkably, raising incidence of OPSCC has been observed in many developed countries over the past few decades. On top of tobacco smoking and alcohol consumption, human papillomavirus (HPV) infection has become a major etiologic factor for OPSCC. The radiotherapy-based or surgery-based systemic therapies are recommended equally as first-line treatment, while chemotherapy-based strategy is applied to advanced diseases. Immunotherapy in head and neck cancer (HNC) is currently under the spotlight, especially for patients with advanced diseases. Numerous researches on programmed death-1 (PD-1)/programmed death-ligand 1 (PD-L1) checkpoint inhibitor, one of the most well-known immunotherapies, are ongoing and have proven immunotherapy benefits in patients with metastatic HNC. In 2016, nivolumab and pembrolizumab were approved as the second-line treatment for advanced metastatic HNSCC by the USA Food and Drug Administration (FDA). Soon after, in 2019, the USA FDA has approved pembrolizumab as the first-line treatment for patients with unresectable, recurrent, and metastatic (R/M) HNC. It has been reported that HPV-positive HNC patients are associated with increased PD-L1 expression; however, whether HPV status indicates different treatment outcomes among HNC patients treated with immunotherapy has contradicted. Notably, HPV-positive OPSCC exhibits significantly better clinical responses to primary treatment (i.e., radiotherapy, surgery, and chemotherapy) and a more desirable prognosis than the HPV-negative OPSCC. Therefore, this review summarizes the previous publications and provides a current immune landscape and future perspectives in OPSCC and the impact of HPV infection in immunotherapeutic efficacy.